Pengaruh Viral Marketing, Social Media Influencer dan Online Customer Review Terhadap Purchase Intention Maybelline Superstay Vinyl Ink pada Mahasiswa UPN Veteran Jatim - Lidia Angelina; Ugy Soebiantoro; Nurkholish Majid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of viral marketing, social media influencers, and online customer reviews on purchase intention for Maybelline Superstay Vinyl Ink products among UPN